Service e-learning in elementary school : : opportunities for learning, teaching and communicating in social space - Mikelić Preradović, Nives (Array, 2012)
The service e-learning project described in this paper presents the development of the educational corner for the institution of primary education. We aimed to motivate the students of information sciences in the Faculty of Humanities and Social Sciences to develop the educational corner that would provide the elementary school teachers and pupils with greater teaching and learning opportunities through interesting educational activities. Our goal was also to motivate the elementary school teachers to realize the importance of communication with their pupils in the social space and to encourage them to use the multimedia educational materials in order to establish better communication and interaction with their pupils. We also aimed to make our students to practically use knowledge and skills acquired through their studies while meeting the demands of global and diverse educational marketplace. Such a project could be attractive to all elementary school teachers searching for ways to incorporate the e-learning into classrooms on both a short-term and long-term basis, to address individual learning traits and spark teaching and learning excitement.